Shaking the coconut business - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
For many people, the coconut symbolizes the relaxed, easy life associated with tropical islands. That may explain why it has often been overlooked As a result, coconut plantations in many countries tend to be over-mature with poor yields and thus...